State of Instructional Educational Facilities of Primary Education at Upazila Level - Alam, Md. Jahangir; Haque, A.K.M. Mahmudul; Kamruzzaman, Muhammad; Hossain, Imran (Universitas Pendidikan Indonesia (UPI), 2023)
Primary education is a basic education for all, which depends on different agencies and factors to ensure its quality. The study assessed the state of instructional facilities in primary education at the Upazila level in Bangladesh. An explanatory sequential design and mixed methods have been used in this study. The researcher has collected quantitative data by surveying primary school head teachers and selected schools from two upazilas: Charghat in Rajshahi and Sundargonj in Gaibandha District. The sample for the study was determined by stratified and simple random sampling. The total schools were 12 and 42 in both study areas. Through different interviews, questionnaire surveys, and document reviews, the researcher has explored the scenario of instructional educational facilities and provided suggestions to ensure quality primary education. The study finds that the Upazila Education Office should be at the vanguard of achieving quality primary education by ensuring the excellence of the school environment through instructional facilities with the help of the government, School Management Committee (SMC), Parent-Teacher Association (PTA), and communities. Overall, the government should prioritize investing in the improvement of instructional facilities in primary schools, as it directly impacts the quality of education and the ultimate academic performance of the students.